HBR's 10 must reads for business students. (HBR's 10 must reads (Series), 2023)
"If you read nothing else to stand out in class and prepare for what's next, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the best ones to help you understand the most important ideas in management, feel confident in business school, and thrive in any role you take on. This book will inspire you to: Think more strategically; inspire and execute innovation; develop marketing plans that deliver competitive advantage; perform at your highest personal level; learn with a growth mindset; redefine what career success looks like to you"--